2018
DOI: 10.1002/ar.24010
|View full text |Cite
|
Sign up to set email alerts
|

Areas of Cartilaginous and Osseous Metaplasia After Experimental Myocardial Infarction in Rats

Abstract: The presence of hyaline cartilage has been previously documented in heart tissue of different vertebrates, ranging from birds to superior mammals. However, there is scarce published data regarding the appearance of focal deposits of hyaline‐like cartilage within the hearts of laboratory rats. Few mechanisms that could trigger the appearance of this type of cartilage in heart were hypothesized (e.g., mechanical stress, ageing). Using different microscopy techniques this report confirms the presence of hyaline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Vascular cartilaginous/osseous metaplasia, which is often associated with the presence of arterial chondrocytes that express type II collagen, is known to be part of the progression of mineralization or atherosclerotic lesion ( Fitzpatrick et al, 2003 ; Nguyen et al, 2012 ). It also provides evidence of cardiac extracellular matrix remodeling for post-infarcted heart and may constitute a supplemental factor for heart failure when it calcifies ( Manole et al, 2019 ; Carreon et al, 2020 ). Cartilaginous metaplasia is considered a potential great risk for arterial wall calcification associated with the atherosclerotic plaque ( Qiao et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular cartilaginous/osseous metaplasia, which is often associated with the presence of arterial chondrocytes that express type II collagen, is known to be part of the progression of mineralization or atherosclerotic lesion ( Fitzpatrick et al, 2003 ; Nguyen et al, 2012 ). It also provides evidence of cardiac extracellular matrix remodeling for post-infarcted heart and may constitute a supplemental factor for heart failure when it calcifies ( Manole et al, 2019 ; Carreon et al, 2020 ). Cartilaginous metaplasia is considered a potential great risk for arterial wall calcification associated with the atherosclerotic plaque ( Qiao et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, bone and cartilage may develop in diseased myocardium. 2 In sheep, the atria are prone to cartilage formation. 3 In mammals, particularly ungulates, the fibrous tissue of the heart may normally contain cartilage or bone.…”
Section: Discussionmentioning
confidence: 99%
“…64 Studies showed that TCs would be injured when normal architecture was detrimental as interstitium cartilaginous and osseous metaplasia in the later stages of myocardial infarction indicated the reaction of cell types or disease microenvironment on TCs. 65 The evidence of TCs heterocellular interaction was provided in recent studies. Inflammation factors induced TCs to provide hepatocyte growth factor to macrophages and transfer from M1 to M1/M2 state.…”
Section: F I G U R Ementioning
confidence: 94%